Activated charcoal toothpastes do not increase erosive tooth wear - Viana, Ítallo Emídio Lira; Weiss, Guilherme Stangler; Sakae, Letícia Oba; Niemeyer, Samira Helena; Borges, Alessandra Bühler [UNESP]; Scaramucci, Taís (Elsevier, 2021)
OBJECTIVES: To assess the effect of activated charcoal toothpastes on enamel and dentin erosive wear. METHODS: Ninety enamel and dentin slabs were randomly distributed into 9 experimental groups (n = 10/substrate): Artificial saliva (negative control); Elmex Caries (EXC - 1400 ppm F- as AmF, reference toothpaste without charcoal); Colgate Luminous White Activated Charcoal (CLW - 1000 ppm F- as MFP); Colgate Natural Extracts (CNE - 1450 ppm F- as NaF); Oral-B 3D White Mineral Clean (OMC - 1100 ppm F- as NaF); Curaprox Black is White (CBW - 950 ppm F- as MFP); Bianco Carbon (BIC - no F-); Natural Suavetex (NSX - no F-); Oralgen Nupearl Advanced (ONA - no F-). Specimens were submitted to a 5-day erosion-toothbrushing abrasion cycling. Surface loss (SL) was determined with an optical profilometer. pH and concentration of available fluoride in the slurries were also assessed. Data were statistically analyzed (α = 0.05). RESULTS: For both substrates, CBW, CNE and EXC had significantly lower SL values than the control. CLW and OMC promoted significantly less dentin wear than the control. All the other groups did not differ significantly from the control. There was a strong negative correlation between SL and concentration of fluoride in the slurries for enamel (r = -0.77) and dentin (r = -0.91), and a strong positive correlation (r = 0.77) between enamel SL and pH. CONCLUSIONS: For both substrates, none of the activated charcoal-based toothpastes resulted in higher SL than brushing with artificial saliva. Only two of the charcoal toothpastes and the reference toothpaste were able to provide further protection against SL. CLINICAL SIGNIFICANCE: Activated charcoal-containing toothpastes are becoming popular, despite the absence of evidence supporting their safety for use by individuals with erosive tooth wear. These products did not pose an additional risk for these subjects. However, it would be preferable to use products that exhibits further protective effect.
Keywords: Activated charcoal toothpaste; Dental erosion; Erosive tooth wear; Optical profilometry; Surface loss; Tooth abrasion